Microstructure modifications and phase transformation in plasma-sprayed WC–Co coatings following post-spray spark plasma sintering - Li, H. (2012)
Thermal sprayed tungsten carbide (WC)–cobalt (Co) coatings have been extensively employed as abrasion/wear protective layers. However, carbon loss (decarburization) of WC–Co powders during thermal spraying reduces the efficiency of the coatings against abrasive wear. Post-spray treatment with spark plasma sintering (SPS) technique was conducted on plasma-sprayed WC–Co coatings in the present study with the aim to compensate the lost carbon in the coatings. X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM) were utilized to characterize the microstructure and phase changes in the coatings brought about through the SPS treatment. Results showed that the rapid SPS technique is successful in supplying superfluous carbon for the restoration of WC in the coating through phase transformation from W2C or reaction with W. Predominant presence of WC was revealed in the coatings treated with SPS at 800 °C and up to 6 min. Furthermore, changes in microstructure, e.g., grain size growth, redistribution of various indigenous phases, were revealed within the coatings after the SPS treatment. It was found that the SPS-induced WC reconstruction can apparently be achieved within the coating surface with limited thickness (<10 μm). Transmission electron microscopy (TEM) results also showed the evidence of supplementary reaction between Co and WC/W2C to form Co3W3C during the SPS processing. Microhardness values obtained on the surface of SPS-treated coating showed ∼40% enhancement over as-sprayed surface.